Public policy and rural tourism development in East Java Province, Indonesia - M. Nilzam Aly; Rahmat Yuliawan; Upik Dyah Eka Noviyanti; Aji Akbar Firdaus; Ari Prasetyo (African Journal of Hospitality, Tourism and Leisure, 2019)
This research mainly focused on introducing the reforms of the public sector and their relevance to rural tourism and discusses the process impacts of the regional regulations towards rural tourism in East Java Province to the current time. Specifically, this research aimed to analyse and identify obstacles which facilitate and may influence the legislation process. A qualitative research method was implemented by using in-depth interviews and questionnaires distributed to stakeholders as respondents. The results of this research shows that experts and rural tourism communities focus group discussions had been involved in the legislative process. Since the upcoming period (2014- 2019) of the Regional Council (DPRD), the regional regulations have still not being issued. A sense of urgency as well as legal protection are increasingly needed for the development plans of rural tourism in East Java to be realised.